The Impact of Corporate Expansion, Financial Liquidity, Profitability, And Solvency on The Issuance of Going Concern Audit Opinions In Manufacturing Firms - Nurdiani, Anny; Kustiawan, Memen; Saepudin, Didin; Evianti, Dessy (Maksi, 2023)
The manufacturing sector plays an important role in economic development. The government is committed to reviving the manufacturing industry through implementing the Making Indonesia 4.0 Roadmap so that it is ready to enter the industrialization 4.0 period. This phenomenon has sparked investors' interest in investing in large markets. However, investors need to know the financial condition of the company that will be given investment funds to be able to consider the profits they will get. The related information was obtained based on the results of an audit by a financial auditor whether the company obtained a going concern permit or not by considering the company's financial condition, such as its growth profile.company, liquidity, profitability, and solvency at that time. This article aims to find out how much influence company growth, liquidity, profitability and solvency have in deciding going concern status by auditors in each company. This article is useful as knowledge information for academics and investors working in the economic field.